2015
DOI: 10.1016/j.clbc.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Survival With Mastectomy or Breast-conserving Surgery Plus Radiation in Young Women Aged < 40 Years With Early-Stage Breast Cancer: A National Registry-based Stage-by-Stage Comparison

Abstract: Introduction/Background Studies have shown that young patients with early-stage breast cancer (BC) are increasingly getting mastectomy instead of breast conserving therapy (BCT) consisting of lumpectomy and radiation. We examined the difference between outcomes in young women (age<40) treated with BCT versus mastectomy. Materials and Methods The Surveillance, Epidemiology, and End Results database was queried for women <40 years of age with stage I–II invasive BC treated with surgery from 1998–2003. Breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
(38 reference statements)
5
44
1
Order By: Relevance
“…Although prior publications have examined surgical choice in young women with mixed results (Table ), there is a growing body of evidence that there is no difference in disease‐free survival or overall survival between operations . Some studies have documented an increased risk of LRR for patients who select BCS vs mastectomy, but this was not seen in our results.…”
Section: Discussioncontrasting
confidence: 54%
“…Although prior publications have examined surgical choice in young women with mixed results (Table ), there is a growing body of evidence that there is no difference in disease‐free survival or overall survival between operations . Some studies have documented an increased risk of LRR for patients who select BCS vs mastectomy, but this was not seen in our results.…”
Section: Discussioncontrasting
confidence: 54%
“…Specifically studying patients under age 40, Donovan et al also reported a 10‐year overall survival disadvantage in unilateral mastectomy patients compared to BCT or bilateral mastectomy (77% vs 85% vs 83%; P < 0.02). However, Vila et al and Ye et al report no survival difference between BCT and mastectomy in women under 40.…”
Section: Resultsmentioning
confidence: 97%
“…17 Rates of bilateral mastectomy have increased despite studies showing a low risk of contralateral breast cancer (0.25%-1.25% annually 18 ) and no consistent literature showing survival benefits. 16,[19][20][21] Most survival studies have also not focused on the younger patients who are driving this trend reversal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several large retrospective analyses of contemporary data have suggested the stage‐adjusted superiority of BCS over mastectomy in early breast cancer in terms of breast cancer‐specific survival and overall survival. Other publications have focused on young women or triple‐negative breast cancer, with the results indicating that BCS is at least as good as mastectomy in terms of survival outcomes. This interesting finding has led some authors to question whether mastectomy without RT should be offered at all as a treatment alternative for early breast cancer, or whether it is time to abandon the ‘mastectomy myth’.…”
Section: Introductionmentioning
confidence: 99%